Adsorption of anionic surfactant (sodium dodecyl sulfate) on silica. Issue 3 (3rd May 2016) - Li, Pengxiang; Ishiguro, Munehide
ABSTRACT: The adsorption of an anionic surfactant sodium dodecyl sulfate (SDS) on a negatively charged silica was studied to provide a better understanding of surfactant adsorption phenomena in an electrostatic repulsion environment between surfactant and soil. The adsorption experiment was conducted under different electrolyte concentration and pH. Results indicated that adsorption happened with hydrophobic interaction, although electrostatic repulsion was generated between SDS and silica surface. The adsorption amount decreased with decreasing electrolyte concentration and increasing pH due to the increase of electrostatic repulsion. The influence of electric potential near the silica surface on the adsorption was confirmed with the modified Langmuir adsorption equation, 1-pK basic Stern model and zeta potential. Because silica is ubiquitous in soils and the water environment, the adsorption characteristics of an anionic surfactant is important when we consider the fate of an anionic surfactant in the environment. The result is also useful when considering the fate of agricultural chemicals which contain negative charge and hydrophobic sites.